What's All This Talk About Assessment? - Frederick Burrack (Academic Chairpersons Conference Proceedings, 2018)
Assessment is more than a hot topic in higher education. It is central to the teaching and learning process. What is assessed reflects what is considered important learning for students in higher education institutions. This closing session is designed to provide clarity as to the purpose of assessment in higher education, responsibilities for academic leaders, and implications for defining what students should learn and the extent to which it has been learned.
Keywords: Assessment Leadership Analysis Informed Teaching